Establishment of an Efficient Regeneration System Amenable to Agrobacterium Mediated Transformation of Two Elite Indica Rice Varieties of North East India - Dey, Mohitosh; Panda, Sanjib Kumar; Sahoo, Lingaraj (International Journal of Applied Sciences and Biotechnology, 2015)
An efficient plant regeneration system from embryogenic callus of two elite indica rice (Oryza sativa spp. indica) varieties of Northeast India, Ketokijoha and Monoharsali is established. The effect of auxin, 2,4-dicholorophenoxy acetic acid (2,4-D) on callus induction was optimized. Friable, nodular and creamish-white embryogenic calli were induced from mature seeds on NB medium supplemented with 2.5 mg/l 2,4-D. Plants were regenerated from 40-50 days old embryogenic callus on NB medium containing 0.5 mg/l BAP (6-benzylaminopurine) and 0.25 mg/l ABA (abscisic acid). Regenerated plants with multiple tillers were rooted on half strength MS medium and rooted plants were acclimatized with 94% survival rate. Higher frequency of callus induction as well as plant regeneration was recorded in Ketokijoha as compared to Monoharsali. The calli of both the varieties were found amenable to Agrobacterium-mediated transformation as evident from strong GUS (β-glucuronidase) expression. The results may find wide application for genetic improvement for valuable traits these elite indica rice varieties of Northeast India. Int J Appl Sci Biotechnol, Vol 3(4): 680-686